TRADISI DALAM PEMBENTUKAN IDENTITAS BANGSA INDONESIA DI ERA MODERN - Tohmat, SaefuI; Syaeful Had, Bambang (Jurnal Cakrawala Pendidikan, 2005)
The Indonesian govemn1ent has often placed the tradition in the periphery ofthe process ofmodernization because it follows the waymO